Thyroid storm without precipitating factors in a previous healthy child: A case report - Takaaki Mori; Marie Mitani-Konno; Yusuke Hagiwara; Yukihiro Hasegawa (Emergency Care Journal, 2022)
The Thyroid Storm (TS) is the severest form of thyrotoxicosis and is associated with a high mortality rate. TS presents with fever, tachycardia, gastrointestinal symptoms, and central nervous system dysfunction and may be overlooked if patients do not present thyrotoxic symptoms or have precipitating factors. We reported a pediatric case of TS with mild proptosis but no obvious precipitating factors in a previously healthy child. A 9-year-old, female patient with a history of attention-deficit hyperactivity disorder presented with the complaint of frequent vomiting. She was alert but lethargic with fever and tachycardia. Physical examination was unremarkable except for coolness in the extremities and a delayed capillary refill time of two seconds. Fluid resuscitation was ineffective in alleviating the tachycardia. Additional history-taking revealed a one-month history of mild proptosis but no other thyrotoxic findings or precipitating factors were found. Markedly elevated thyroxine and triiodothyronine and suppressed thyroid-stimulating hormone on thyroid function tests led to a diagnosis of TS. Methimazole, potassium iodine, bisoprolol, and hydrocortisone were administered. Her vital signs and thyroid functions gradually improved, and she was discharged 18 days after admission without any serious complications. She is currently euthyroid and clinically stable on 5 mg of methimazole at three months after admission. When tachycardia that is resistant to usual resuscitation is found, careful history-taking and physical examination targeting thyroid disorders should be performed to assess for TS.